Italian Validation of the Touch Avoidance Measure and the Touch Avoidance Questionnaire - Casetta, Laura; Rizzi, Luca; Passarelli, Marcello; Arcara, Giorgio; Perrella, Raffaella (Frontiers in Psychology, 2020)
Social touch is essential in relationships and wellbeing, but the unique personal experience of touch is not assessed and taken into account in health and social care services. The pleasantness of gentle stroking is influenced by genre, toucher genre, toucher familiarity, culture, and age. Moreover, pleasantness is influenced by touch avoidance, the attitude towards interpersonal touch. The aim of this article is to present the translation, adaptation, and validation in Italian of two scales to measure touch avoidance. For translation and validation, we selected the most used scale, the Touch Avoidance Measure (TAM; Andersen & Leibowitz, 1978) and a more recent scale, the Touch Avoidance Questionnaire (TAQ; Ozolins & Sandberg, 2009). Confirmatory factor analyses reported good model fit for the TAM (CFI = .947, TLI = .940, RMSEA .065) and excellent model fit for the TAQ (CFI = .954, TLI = .950, RMSEA = .058). Internal consistency was high for all subscales, except the TAQ “Stranger” subscale. One-month test-retest reliability ranged from .67 to .90 for each subscale. Lastly, convergent validity between the TAM and TAQ has also been found to be high. We conclude the TAM and TAQ can be used to assess touch avoidance among Italian population. The instrument can be used to support healthcare professionals and to assess the attitude toward touch in individuals with interpersonal difficulties.